Goethite aging explains Ni depletion in upper units of ultramafic lateritic ores from New Caledonia. (1st July 2015) - Dublet, Gabrielle; Juillot, Farid; Morin, Guillaume; Fritsch, Emmanuel; Fandeur, Dik; Brown, Gordon E.
Abstract: An upward loss of Ni is commonly reported in the oxide-rich unit of Ni-laterite deposits developed over ultramafic rocks in tropical regions, especially in freely drained and deeply weathered regoliths. Because goethite is the major mineral constituent of such oxide-rich units, this Ni loss has been linked to compositional changes in goethite. In the present study, we have investigated possible correlations between Ni contents in the bulk laterite, and the evolution of goethite in terms of composition and crystallinity, in two Ni-rich and one Ni-poor lateritic profiles from New Caledonia. Ni K-edge Extended X-ray Absorption Fine Structure (EXAFS) spectroscopy indicates that goethite hosts the main fraction of Ni in the three profiles investigated. Asbolane/lithiophorite identified as accessory minerals by X-ray diffraction (XRD) have little effect on the vertical variations in bulk Ni content in spite of the fact that the Ni contents of these Mn-oxides can be significant at certain depths. The gradual decrease in Ni content from the bottom to the top of the three Ni lateritic profiles correlates with a decrease in the Ni content of goethite as determined by electron probe micro-analysis. In addition, XRD data show that these compositional trends are linked to an increase of the mean coherent domain size of goethite. These observations support the hypothesis that Ni is expelled from goethite as it ages through successive dissolution and recrystallization cycles during the lateritization process. Comparison of laterites having different degrees of weathering suggests that this aging process could also play a significant role in the regional variability of Ni content in Ni-laterite deposits.